Soft Power Sebagai Instrumen Peningkatan Ekonomi Korea Selatan: Popularitas Bangtan Sonyeondan (BTS) Tahun 2018-2020 - Indah Lestari, I Gusti Ayu; Sushanti, Sukma; Intan Parameswari, Anak Agung Ayu (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
South Korea is a nation who have been using popular culture as soft power. By taking advantage of the popularity of popular culture, South Koreans fulfill their national interests. This study analyzes the phenomenon of global popularity of Bangtan Sonyeondan (BTS) and its impact on the improvement of the South Korean economy. BTS' global popularity is used as an extension of the government in the international world. Through BTS, the South Korean government affect the perceptions and preferences of the international community. Starting from public interest in BTS as a product of South Korean popular culture, then develop into interest of South Korean products and ultimately enhance the positive image of the country. Key Words: Soft Power, Bangtan Sonyeondan, Economic Improvement.